KEPEMIMPINAN PENGHULU BAGAN CEMPEDAK KECAMATAN RANTAU KOPAR KABUPATEN ROKAN HILIR 2018-2021 - Suci Rahmadani; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to analyze the role of leadership and the community's perspective on participation in self-help development in the Bagan Cempedak Village, Rokan Hilir Regency. This is important because the development of rural areas has so far been the main theme in development and participation studies. The definitive village head Bagan Cempedak and the headship administration can encourage the community to be directly involved in the development process with a self-help or gorong royong pattern. This condition can be seen from the high participation of the Bagan Cempedak village. This research is a descriptive qualitative research with a qualitative approach. The subjects of the research were the princes and the apparatus village, community leaders, youth leaders and the Bagan Cempedak village community. Researchers are the main component in research with the help of interview guidelines, documentation and data analysis. The data analysis technique used is data collection, data reduction, data presentation and drawing conclusions to explain the validity of the data by using sources. The results of this study is the role of leadership as a motivator and communicator with direct involvement in every process of infrastructure development, active Penghulu in embracing the community, coordination and communication of all groups and layers of society are well established. In addition, the community's perspective on participation in self-help development gains support, trust, and responses as well as community involvement in the process of development activities, both in the form of money (objects), thoughts (ideas or ideas), as well as in the form of labor (gotong royong). Keywords: Leadership, Participation and Development Self Help.